Educação ambiental entre os Carnavais dos amores com os mascarados do congo de Roda D'Água - Ramos, Andreia Teixeira (2013)
This dissertation is an invitation to the meetings and movements of a research in Environmental Education (EE), that is inspired in cartography and studies about the everyday and linking the conversations of the problematic field. The aim of this work was to map and discuss in the present, the socio-environmental knowledge-doings, of the art of doing and narrate the production of the Mascarados do Congo de Roda d/ Água (the Masked characters of the community of Roda d/ Água), Cariacica (ES) and the crossings with everyday school netwroks and other living spaces. Our bet is to think the creation of autopoietic EE that happens during the invention of the self and the world with the production of the Mascarados. We thought about the autopoietic EE reading the studies of Humberto Maturana, unmasking clues that move our relations and collective human experiences in the language empowering ontological, ethical, political and aesthetic dimensions of talking and being sustainable. In everyday inventiveness, our desire was follow the processes of the Mascarados production, secular character of the municipality of Cariacica through flows, encounters, stories, conversations, lines, shapes, forces, entering the crossing and leaving them to cross through us. The inventions of everyday experiences that emerge with the socio-environmental knowledge-doings, in a place of tensions, conflicts and negotiations with networks of conversations, also creating relationships of collectivity, solidarity and acceptance of the other as a legitimate other with us. This research runs crossings inspired by the works of Alves (2010), Carvalho (2008; 2009 and 2011), Certeau (2008a and 2008b), Deleuze (1992), Ferraço (2003 and 2005), Guattari and Rolnik (2011), Kastrup (2009), Larrosa (2004), Passos et al. (2009), Maturana (1997; 1998; 2006), and Tristão (2004 e 2012), creating meetings, disagreements, rhizomatics meetings, a wire pulling the other , and citing Deleuze (1992), each person, as a whole is already a lot.. always working on several.